A molecular quantitative trait locus map for osteoarthritis - Julia Steinberg (Nature Portfolio, 2021)
Understanding the molecular effects of disease variants in relevant tissues is essential to understanding and treating disease. Here, the authors discover expression and protein quantitative trait loci in cartilage and synovium from 115 osteoarthritis patients to pinpoint genes of action and potential drug treatments.